Landscape of T‐cell repertoires with public COVID‐19‐associated T‐cell receptors in pre‐pandemic risk cohorts. Issue 9 (28th August 2021) - Simnica, Donjete; Schultheiß, Christoph; Mohme, Malte; Paschold, Lisa; Willscher, Edith; Fitzek, Antonia; Püschel, Klaus; Matschke, Jakob; Ciesek, Sandra; Sedding, Daniel G; Zhao, Yu; Gagliani, Nicola; et al.
Abstract: Objectives: T cells have an essential role in the antiviral defence. Public T‐cell receptor (TCR) clonotypes are expanded in a substantial proportion of COVID‐19 patients. We set out to exploit their potential use as read‐out for COVID‐19 T‐cell immune responses. Methods: We searched for COVID‐19‐associated T‐cell clones with public TCRs, as defined by identical complementarity‐determining region 3 (CDR3) beta chain amino acid sequence that can be reproducibly detected in the blood of COVID‐19 patients. Of the different clonotype identification algorithms used in this study, deep sequencing of brain tissue of five patients with fatal COVID‐19 delivered 68 TCR clonotypes with superior representation across 140 immune repertoires of unrelated COVID‐19 patients. Results: Mining of immune repertoires from subjects not previously exposed to the virus showed that these clonotypes can be found in almost 20% of pre‐pandemic immune repertoires of healthy subjects, with lower representation in repertoires from risk groups like individuals above the age of 60 years or patients with cancer. Conclusion: Together, our data show that at least a proportion of the SARS‐CoV‐2 T‐cell response is mediated by public TCRs that are present in repertoires of unexposed individuals. The lower representation of these clones in repertoires of risk groups or failure to expand such clones may contribute to more unfavorable clinical COVID‐19 courses. Abstract : Simnica et al . report on public T‐cell receptors in immune responses to SARS‐CoV‐2, which are shared between patients and non‐exposed individuals. Their lower prevalence in older age and cancer could imply why these risk groups may experience more severe COVID‐19 courses.